The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph18084018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hospital Nurses’ Perception on Clinical Alarms and Patient Safety Culture on Alarm Management Practice

Abstract: This study aimed to identify the impact of nurses’ perception of clinical alarms and patient safety culture on alarm management. Additionally, we aimed to describe the importance of clinical alarm issues. The data were collected from 21 August to 10 September 2020. The study participants were 116 nurses working in a tertiary acute care hospital in Korea. The self-report questionnaire included general characteristics, clinical alarm issues, nurses’ alarm perception, patient safety culture, and alarm management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Currently, there exist numerous issues in the nursing work in most hospitals, such as the uneven distribution of human resources and the pressure on nursing work, which downgrades the quality of nursing in hospitals [10]. Zhang et al [11] have found that a scientific and effective management model for nursing staff contributed to improving nurses' sense of responsibility and mobilizing their enthusiasm for work which effectively ensures the integrity and continuity of nursing [12]. In traditional nursing management, the inconsistency of nursing quality due to the individual differences of nurses may result in poor nurse-patient relationships [13].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there exist numerous issues in the nursing work in most hospitals, such as the uneven distribution of human resources and the pressure on nursing work, which downgrades the quality of nursing in hospitals [10]. Zhang et al [11] have found that a scientific and effective management model for nursing staff contributed to improving nurses' sense of responsibility and mobilizing their enthusiasm for work which effectively ensures the integrity and continuity of nursing [12]. In traditional nursing management, the inconsistency of nursing quality due to the individual differences of nurses may result in poor nurse-patient relationships [13].…”
Section: Discussionmentioning
confidence: 99%
“…Participants identified the item “Frequent false alarms, which lead to reduced attention or response to alarm when they occur,” as the most important issue. Participants in previous studies have also attached the greatest importance to this issue, implying that the problems caused by false alarms persist 2,10,12,16,17 . In terms of alarm fatigue, more than half of the participants in this study indicated that false alarms occur frequently.…”
Section: Discussionmentioning
confidence: 59%
“…Participants in previous studies have also attached the greatest importance to this issue, implying that the problems caused by false alarms persist. 2,10,12,16,17 In terms of alarm fatigue, more than half of the participants in this study indicated that false alarms occur frequently. Two-thirds of the nurses perceived that false alarms contribute to a lack of response by several nurses.…”
Section: Discussionmentioning
confidence: 70%
“…The findings agreed with other study that nurses with different years of nursing work had no statistical significance in their commonly used monitors' alarm response fatigue and also no job position recognize relation with alarm fatigue and female nurses, charge nurses, and nurses who work less than 40 h per week were more likely have a relationship with alarm fatigue. 25 Another study result also shows that high-level positions, long working years, high professional titles, and high education are negatively correlated with alarm fatigue. 26 Notwithstanding the interesting results, this research has some limitations.…”
Section: Part Ii: Relationship Between Nurses' Alarm Fatigue and Vari...mentioning
confidence: 94%